THE EFFECT OF PROFIT SHARING ON SAVING INTEREST IN ISLAMIC MICRO FINANCE - Arifa, Nurin Ilma; Ulfah, Indar Fauziah; Anis, Muhammad (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
In Mojogedang District, the majority of the population is Muslim, but there are still many people who don't understand what BMT is and prefer to save in conventional cooperatives. This is caused by the interest in conventional cooperatives, which they consider as profit. Meanwhile, Baitul Maal Wat Tamwil (BMT) does not apply an interest system, but instead uses a profit sharing system. The interest system is something that is prohibited in Islamic sharia. This research aims to find out how the profit sharing system influences customers' interest in saving at Baitul Maal Wat Tamwil (BMT) Sapu Jagad Nusantara in Mojogedang District. This research is a quantitative study that applies simple linear regression analysis and uses purposive sampling techniques. Primary data was obtained through a questionnaire distributed to 100 respondents via Google Form, with previously determined respondent characteristics. The research results show that profit sharing has a significant influence on interest in saving at BMT Sapu Jagad Nusantara, Mojogedang District. Evidence of this can be seen in the simultaneous test (F Test), where the significance value is 0.000 which is smaller than (<) 0.05, and the calculated F value reaches 44.767.